A Critical Review of Gadget-Induced Infertility Claims and a Comprehensive Reproductive Etiology Analysis - Resti Aulia Fitri (Rajaki of Tulip Medika Publisher, 2025)
Infertility represents a massive global public health challenge, affecting approximately 17.5 percent of the adult population worldwide, or approximately 1 in 6 people, with limited variation between high- and low-income regions. This review aims to provide a comprehensive analysis of the etiology of male and female reproductive health and to critically evaluate the validity of popular claims about infertility caused by electronic device use. The methodology used is a critical review of the scientific literature, focusing on mechanistic evidence of thermal and radiation risks, complemented by epidemiological analysis from the Global Burden of Disease (GBD) 2021. The results indicate that the risk of male infertility from laptops on the lap is a measurable clinical fact, as it causes scrotal hyperthermia that impairs spermatogenesis. In contrast, claims regarding mobile phone radiation (RF-EMF) remain inconclusive in the human population, with high uncertainty. The main etiologies of female infertility are dominated by Ovulatory Disorders (especially PCOS) and advanced maternal age. In contrast, male infertility is mainly associated with Varicocele (the most common treatable cause) and idiopathic conditions such as Oligoasthenoteratozoospermia (OAT). In conclusion, infertility is a multifactorial condition, and the main recommendations should focus on thermal risk mitigation as well as first-line metabolic intervention through weight management, considering that obesity is a major metabolic modifier.